PELAKSANAAN PEMBERIAN IZIN USAHA PERTAMBANGAN MINERAL DAN BATU BARA (MINERBA) DI KABUPATEN PANDEGLANG SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Thelisia Kristin; Rasji Rasji (Jurnal Hukum Adigama, 2019)
Nation Authority are held by Government. That authority divided into several regions in indonesia. That regions devided according to article 18, Chapter (1) UUD 1945, stated that United Nation are devided into several provinces, and each province divided into region and city, which in every provinces, Regency,  and Cities have they own regulation that have been continued arranged at Article 18 Chapter (2) UUD 1945 that stated every appointed government in every provinces, regency, and cities have authority to arranging and managing they own government errand according to autonomy principal and helper task.  This thing have a tight connection with nation purposes to protect, to prosper and to involved in world order. And for that reason act number 32 - 2004 about region goverment are made that stated about more clearly about  goverment power distribution which held by nation.  But about exploitation abundance natural resources, especially in mining sectors, act 4 - 2009 are made to regulate minerals and coal mining operation. In Act 4- 2009 are regulating provinces, Regencies, and cities government jurisdiction to make  warrant for mining operations. But in practices there's often issues come out about jurisdiction between provinces,  regencies, and cities goverment. Which in time,  act 32- 2004 are replaced with act 23 - 2014. The writing of a thesis this will discuss the situation in further information about of execution in the provision of licenses for and the obstacles faced all that is in issuing of the business licenses after the entry into force of the country mines in solidarity act 23 – 2014 that is the newest. Reserach methode that writer used is yuridis normatif which is a descriptive method And writer also use act approaches.